Macrophage Activity and Histopathological Differences of Lung Tissue on Sequential Co-infections of Heligmosomoides Polygyrus Nematode on Mycobacterium Tuberculosis Infection - Laksmi Wulandari1.2, Muhammad Amin1, Soedarto3, Gatot Soegiarto2.4, Kenji Ishiwata5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Tuberculosis is a chronic infection caused by Mycobacterium tuberculosis, a facultative intracellular parasite, that can be eliminated by cellular immunity played by macrophages. It has become a debate whether the co-infection of nematodes will affect the immune response of macrophages towards mycobacterium infection. Objective: To reveal macrophage activity and histopathological difference of lung tissue in sequential coinfection of Heligmosomoides Polygyrus towards Mycobacterium tuberculosis infection. Method: This study used 49 mice divided into 7 treatment groups with Mycobacterium tuberculose infection by inhalation and Heligmosomoides polygyrus orally within 8 and 16 weeks, and observed by immunohistochemical staining. Result: Infection for 8 weeks showed polarization of macrophages towards M1 macrophage, whereas in 16 weeks, the macrophage polarization more towards M2 macrophages, supported by histopathological changes of lung tissue: peribronchiolitis, perivaskulitis, alveolitis, and granuloma formation with counts of acid-resistant germs +3. There was a difference of expression of arginase1 to each group (p <0.001) and there was a difference of T CD4+ Th1 lymphocyte (p <0.001). Conclusion: There is a difference in macrophage activity in lung tissue; however, it does not cause different levels of histopathological changes in lung tissue and does not affect the immune response to Mycobacterium tuberculosis infection.